Kombinasi nanoemulsi Minyak Kemiri (Aleurites mollucana L.) dan Serbuk Daun seledri (Apium graveolens L.) pada Model Penyakit Alopesia - Yonathan Tri Atmodjo Reubun; Anggelina Aprilia Pangalila (Jurnal Farmasi Indonesia, 2023)
Candlenut oil and celery leaves have been widely used by people in the world as a treatment for hair loss problems as well as strengthening hair roots and blackening hair. Hair loss disease or in the medical world called alopecia is a disease where the amount of hair loss is more than hair growth in general. The main cause pf alopecia generally occurs due to inflammation in the hair follicles. The purpose of this experimental animals used, namely male rabbits of the New Zealand White type. The study began by testing the phytochemical screening on each of the materials used. Furthermore, a combination of candlenut oil and celery powder was carried out to form a nanoemulsion preparation. After that, tests were carried out including pH, emulsion type, hair growth including hair weight and thickness of the shaving area. The results showed that the co,bination of candlenut oil and celery powder had a pH value of 6.30 with an emulsion type, namely oil in water (O/W) and had hair growth activity from test animals for 28 days with the average weight and thickness of hair 0.2458 and 1,15 cm. this result is better than average positive control product X with an average weight and thickness of 0.2076 and 1 cm. in addition, compared with the negative control, the results of weight and hair thickness were 0.0305 and 0.5 cm. based on these results, it was concluded that the combination of candlenut oil and celery powder had good hair growth activity in experimental animals so that it could be used as treatment therapy for alopecia patients.